“Dejar hacer”, “dejar correr”. Procesos económicos de inmigrantes en países desarrollados - Pérez González, Beatriz (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
The article is focused on the difficulty that the immigrants have to faced the economic processes in the developed countries. It also proposes the alternative of making it from the family economies, with strategies of common action, using the advantageous features of the domestic economy inside a market full of products and starting from marginal employments.